HISTORY OF DISCRESSION AND ELEMENTS ABUSE THE AUTHORITY IN CRIMINAL CORRUPTION IN INDONESIA - yulianti, Lulu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
Indonesia is one of the countries that adheres to the concept of the state law which is closely related to the principle of legality as a guarantee of legal certainty for the people and the country. However, there is often a legal vacuum due to the rapid development of human needs. This problem is certainly not all can be arranged in detail in legislation in writing, because it will cause over regulation. Therefore, discretion must be a solution to fill the legal vacuum in line with the development of human needs. Discretion is certainly not necessarily without the burden of accountability. Maladministration often occurs in the implementation of discretion which results in criminal liability for corruption and legal liability for state administration. To find out the concept of discretion and place it in appropriate judicial competence, it is necessary to review the history of the concept of discretion and the history of the element of abusing authority which is closely the case with the concept of discretion. In this research, we will discuss the history of the concept of discretion in Indonesiay And the history of abusing authority in Indonesia is divided into 3 periods, namely the period before independence, the new order and reformation.